Kejahatan Korporasi dan Kerugian Negara dalam Analisis Yuridis Korupsi dalam Tata Niaga PT Timah Tbk - Amalia Solikha; Peni Nurmaliza; Rahayu Sri Utami (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
Corporate crime in the natural resources sector is a legal phenomenon that has a broad impact on state finances and public interests. This article analyzes the legal case of tin trade corruption involving PT Timah Tbk, a state-owned enterprise managing a strategic commodity. This study aims to examine the construction of corporate crime and the legal implications of state financial losses arising from deviant trade practices. The research method used is normative legal research with a juridical-analytical approach through a review of laws and regulations, legal doctrine, and relevant legal facts. The results of the study indicate that tin trade corruption is a systemic corporate crime integrated into the company's policies and business mechanisms, so that criminal liability cannot be limited to individuals alone. The resulting state losses are multidimensional, including fiscal losses, loss of potential revenue, and violations of the principle of state control over natural resources. This study emphasizes the importance of strengthening corporate criminal law enforcement to maintain the integrity of state-owned enterprises and protect state interests.